2001
DOI: 10.1039/b007163n
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidine annelated heterocycles - synthesis and cycloaddition of the first pyrimido[1,4]diazepine N-oxides

Abstract: 5-Formyl-and 5-acetyl-4-(alkenylamino)pyrimidines 5 have been prepared as precursors to novel pyrimido [1,4]diazepine N-oxides 3. In addition to cyclisation to the targeted dipoles the substrates 5 have also been observed to form imidazopyrimidines 12 and 39 via an intramolecular Michael addition; additionally 5b has been observed to form the pyrimidoazepinone 42. Aldonitrone 3a cycloadded readily to olefinic dipolarophiles; ketodipole 3b did not share this reactivity. Both dipoles reacted with acetylenic dipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The resonance signals for 6a (CDCl 3 , room temperature) were sharp suggesting either that the tricyclic framework adopts a single preferred conformation or that equilibration between conformational isomers is very rapid at room temperature. This observation is in line with our earlier finding that the isoxazolobenzodiazepinones 7 11 and the isoxazolopyrimidodiazepinone 8 12 have sharp pmr spectral signals, on the other hand Romeo's related tricycles, e.g. 9 (R = Et, Me) exist as a mixture of slowly interconverting diastereomers 13,14 .…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The resonance signals for 6a (CDCl 3 , room temperature) were sharp suggesting either that the tricyclic framework adopts a single preferred conformation or that equilibration between conformational isomers is very rapid at room temperature. This observation is in line with our earlier finding that the isoxazolobenzodiazepinones 7 11 and the isoxazolopyrimidodiazepinone 8 12 have sharp pmr spectral signals, on the other hand Romeo's related tricycles, e.g. 9 (R = Et, Me) exist as a mixture of slowly interconverting diastereomers 13,14 .…”
Section: Resultssupporting
confidence: 81%
“…We have previously observed that the analogous isoxazolobenzodiazepinones 21 have sharp pmr and 13 C nmr spectral signals at room temperature 7,11 whilst similar adducts, e.g. 22 from Aversa's laboratory 14 and the isoxazolopyrimidodiazepine 23 which we have recently reported 12 , display signal duplication and signal broadening respectively at room temperature. Upon perusal of the pmr spectral characteristics (room temperature) of the aforementioned molecules it is apparent that the conformational freedom of the 5,7,6-tricyclic framework is not easily predictable.…”
Section: Figurementioning
confidence: 99%
“…The rearrangement likely proceeds by a mechanism parallel to that previously suggested for the oxa analogue 15d. 21 The pyrroloketopiperazine skeleton is found infrequently in the chemical literature, however it does occur naturally in the alkaloid peramine 17. 22 The marine metabolites longamide 18a, and hanishin, 18b, also have a 3,4-dihydropyrrolopiperazinone framework.…”
Section: Introductionmentioning
confidence: 99%
“…The facility of S N Ar displacement for halopyrimidines follows a predictable order, as shown here. Nucleophilic aromatic substitution reactions have also been commonly applied to the transformation of pyrimidines into introduce a wide variety of new hetero and carbon ring substituents, as illustrated in Scheme 19.150 [168].…”
Section: With Replacement Of Good Leaving Groupsmentioning
confidence: 99%